Women partners leaving the firm: Choice, what choice? - Anderson, Deirdre A.; Vinnicombe, Susan; Singh, Val (Emerald, 2010)
This paper is based on the experiences of 31 women who have recently left partner roles within an international management consultancy firm. The purpose of this paper is to explore discursively their perceptions of choice within their decisions to leave. Design/methodology/approach - Data were collected from 31 women using semi-structured telephone interviews, a 66 per cent response rate. A discursive approach to analysis was adopted. Findings - The decision to leave is the culmination of many interacting factors at a time when a financial incentive for resignation is available. Findings present here focus on discourses of loyalty to and affection for the company and work-life integration. Research limitations/implications - Limitations include access only to women who have left the firm, allowing for no comparison with those who were still partners. Additionally, we were unable to speak to any of the male partners who have left the firm in the same timescales, although in smaller proportions. Practical implications - The findings indicate the need to review the excessive time demands placed on partners and provide further support for policies, which enable greater flexibility. Originality/value - This paper uses data from a rare sample of women, those who have actually left senior roles within one organization.
Keywords: MT=DPGC